CRITICAL LITERACY THROUGH GRAPHIC NOVELS: A CASE FOR INDIAN LIBRARIES FOR SUSTAINABLE PEDAGOGY - R., Abinaya; M., Angkayarkan Vinayakaselvi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper examines the role of graphic novels in fostering critical literacy, underscoring libraries as a space to promote this skill. It highlights how the visual-verbal medium of graphic novels inculcates critical and creative thinking and comprehension. The paper advocates for the inclusion of graphic novels in Indian libraries, contributing to education and sociocultural development. The paper begins with a fundamental reading to define critical literacy and graphic novels, followed by close reading and visual-verbal analysis of select Indian graphic novels to demonstrate their capacity to foster critical literacy. The paper employs Ciardiello’s (2004) critical inquiry practices as the theoretical framework.